Dendrimeric Epoxy Resins Based on Hexachlorocyclotriphosphazene as a Reactive Flame Retardant Polymeric Materials: A Review - Dagdag, O.; Bachiri, A. El; Hamed, O.; Haldhar, Rajesh; Verma, Chandrabhan; Ebenso, Eno; Gouri, M. El (Journal of inorganic and organometallic polymers and materials, 2021)
In the present review article current developments on hexachlorocyclotriphosphazene (HCCP) based epoxy resins as reactive flame retardants is surveyed. The cyclotriphosphazene in its monomeric and polymeric forms behave as flame retardants due to the presence of phosphorus (P) and nitrogen (N) atoms. Usually hexachorocyclotriphosphazene based epoxy resins show reasonably low thermal and fire retardant properties therefore some external additives are being added to improved their thermal and fire retardant properties. Present review article describes the collection of previous works published on the flame retardant properties of hexachlorocyclotriphosphazene based epoxy resins. Present article also deals with the surface modification, functionalization and description of various hexachlorocyclotriphosphazene based epoxy resins as thermal and flame retardants.